PANDANGAN TOKOH MASYARAKAT TERHADAP PERNIKAHAN USIA DINI DI KAMPUNG MALAUS DISTRIK SALAWATI KABUPATEN SORONG - Een Iriyana; Mohammad Arafah Idrus (Prodi Akhwal Syahsiyyah IAIN Sorong, 2021)
Early marriage is a marriage that is carried out according to the terms and conditions, but one of the bride and groom or both the bride and groom are not yet mature and are not psychologically ready to carry out household responsibilities. Early marriage can also be interpreted as marriage carried out at an age under the provisions of the marriage law. This study was carried out to know the process of early marriage in Malaus Salawati village, Sorong district, the community's view of early age in Malaus village, Salawati district, Sorong district, and the impact of early age in Malaus village, Salawati district, Sorong district. This study uses qualitative research methods, this type of research is used to collect data using observation, interviews, and documentation. The location of this research is Malaus village, Salawati district, Sorong district. Then the respondents from this study were the head of the Malaus village and several community leaders in the Malaus village, Salawati district, Sorong district. The results of this study indicate that the early age that occurs in Malaus village, Salawati district, Sorong district is influenced by several factors, the first is a weak family economy, the second factor is the low understanding of teenagers due to dropping out of school and thirdly this happens because it occurs outside of marriage.